Can Hierarchy Dodge Bullets? Examining Blame Attribution in Military Contracting. (September 2019) - Johnson, Austin P.; Geva, Nehemia; Meier, Kenneth J.
The increased outsourcing of national security endeavors to private military companies (PMCs) raises questions concerning public evaluations of their performance and the extent to which government officials are held accountable. We use a survey experiment to test public blame attribution associated with a failed military operation that was conducted by either regular or private military personnel. Our findings suggest that there are multiple mediating pathways in the process of attributing blame in foreign policy. Furthermore, our findings suggest that contracting out military functions to a PMC can damage perceptions of performance, perhaps increasing blame attribution by the public. These impacts on the attribution of blame suggest that PMCs are viewed as inferior service providers by the mass public and politicians will be held accountable, directly or indirectly. Implications from our study add to the discussion on the outsourcing of military capacities which are rapidly expanding in the Western world.